A study of the psychiatric-mental health nursing practice of two categories of nurses in Suan Prung Psychiatric Hospital. - Bannajakra, Suewapan
This study was carried out to gather baseline data of existing practice in psychiatric-mental health nursing (PMHN) by the 2 categories of nurses at San Juan Psychiatric Hospital in Northern Thailand. It has 3 objectives, namely, to: (1) obtain baseline data about the scope of practice of psychiatric-mental health nursing at this hospital; (2) investigate the practice of psychiatric-mental health nursing activities which were practiced by the professional nurses group and the technical nurses group; and (3) identify some nurses' characteristics which affect their practice of psychiatric-mental health nursing. All psychiatric nursing personnel (106 nurses) were the population of this study. They included the professional nurses and the technical nurses. Data were gathered using the questionnaire as the research tool. The data obtained were analyzed by using the percentage, the Z test and the Chi-squared test as the statistical procedures. The results of the study revealed that the scope of practice in psychiatric-mental health nursing by the 2 categories of nurses at San Juan Psychiatric Hospital covered 9 major activities namely: (1) providing the therapeutic milieu; (2) assuming the surrogate parents role; (3) assuming the role of social agent; (4) working with patients concerning the here-and-now problems; (5) caring for the somatic aspects of the patients' health problem; (6) conducting psychotherapy; (7) teaching factors related to emotional health; (8) providing leadership to other personnel; and (9) engaging in social and community action related to mental health. Among this 9 activities, the nurses practiced or performed less on the 9th major activity which involved engaging in social and community action related to mental health. The results indicated that the technical nurses group had more opportunities to perform nursing activities under the first 5 major activities. The professional nurses group had more opportunities to perform nursing activities which were under the 6th, 7th, 8th and 9th major activities. Using the Z test it was, however revealed that there is no significant difference between the psychiatric-mental health nusing practice of these 2 categories of nurses. Using the Chi-squared test, it was also revealed that there is no significant relationship between the level of nursing educational background and the practice proficiency of the nurses. Using the same statistics procedure, the study showed that there is no significant relationship between the years of experience in psychiatric service setting and the practice proficiency of the nurses. The study also revealed that there is no significant relationship between the experience in attending an in service program during the last 5 years and the practice proficiency of the nurses.